2014
DOI: 10.1016/j.jbankfin.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Testing for a break in the persistence in yield spreads of EMU government bonds

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 39 publications
(33 reference statements)
2
46
0
Order By: Relevance
“…Using the German interest rate as a benchmark rate, Sibbertsen, Wegener, and Basse [40] examined whether bond yield spreads in Spain, France, and Italy may experience structural breaks. They found that there were breaks of the bond yield spread during 2006-2008 and that bond yield spreads rose substantially after 2008 mainly due to higher sovereign credit risk related to the sovereign debt crises.…”
Section: Literature Surveymentioning
confidence: 99%
“…Using the German interest rate as a benchmark rate, Sibbertsen, Wegener, and Basse [40] examined whether bond yield spreads in Spain, France, and Italy may experience structural breaks. They found that there were breaks of the bond yield spread during 2006-2008 and that bond yield spreads rose substantially after 2008 mainly due to higher sovereign credit risk related to the sovereign debt crises.…”
Section: Literature Surveymentioning
confidence: 99%
“…Changes in the order of integration have been documented in a number of macroeconomic and financial variables, such as output (De Long and Summers, ), the budget deficit (Hakkio and Rush, ), inflation (Halunga et al , ; Kumar and Okimoto, ; Hassler and Meller, ). Financial studies include the analysis of financial market bubbles (Sollis, ; Frömmel and Kruse, ), international and sectoral bank equity index returns (Hassler et al , ), yield spreads of EMU government bonds (Sibbertsen et al , ). Interest in the characterization of the degree of persistence and in its potential instability is particularly strong in the evaluation of macroeconomic policies such as inflation targeting because ceteris paribus a reduction of the order indicates a tighter control of the variable of interest (provided that the process is mean reverting, at least after the change).…”
Section: Introductionmentioning
confidence: 99%
“…They apply the test to U.S. inflation data and find a break in the early 1980s. Sibbertsen et al (2014) test for the persistence of EMU government bond yields for France, Italy and Spain, using the same methodology, and find breaks between 2006 and 2008.…”
Section: Introductionmentioning
confidence: 99%